Interpretation and literature in early medieval China - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2010)
Early medieval China, spanning the period from the last years of the Eastern, or Later Han dynasty (second century C.E.) to the early Tang in the seventh century, marks an era of profound change in Chinese history.